Transposable Element Insertions in Long Intergenic Non-Coding RNA Genes - Kannan, Sivakumar; Chernikova, Diana; Rogozin, Igor B.; Poliakov, Eugenia; Managadze, David; Koonin, Eugene V.; Milanesi, Luciano (Frontiers in Bioengineering and Biotechnology, 2015)
Transposable elements (TE) are abundant in mammalian genomes and appear to have contributed to the evolution of their hosts by providing novel regulatory or coding sequences. We analyzed different regions of long intergenic non-coding RNA (lincRNA) genes in human and mouse genomes to systematically assess the potential contribution of TEs to the evolution of the structure and regulation of expression of lincRNA genes. Introns of lincRNA genes contain the highest percentage of TE-derived sequences, followed by exons and then promoter regions although the density of TEs is not significantly different between exons and promoters. Higher frequencies of ancient TEs in promoters and exons compared to introns implies that many lincRNA genes emerged before the split of primates and rodents. The content of TE-derived sequences in lincRNA genes is substantially higher than that in protein-coding genes, especially in exons and promoter regions. A significant positive correlation was detected between the content of TEs and evolutionary rate of lincRNAs indicating that inserted TEs are preferentially fixed in fast-evolving lincRNA genes. These results are consistent with the RIDL (Repeat Insertion Domains of LncRNAs) hypothesis under which TEs have substantially contributed to the origin, evolution, and in particular functional diversification, of lincRNA genes.